2010
DOI: 10.1002/ptr.3213
|View full text |Cite
|
Sign up to set email alerts
|

Blueberry anthocyanins and pyruvic acid adducts: anticancer properties in breast cancer cell lines

Abstract: The purpose of this study was to investigate the anti-cancer properties of an anthocyanin-pyruvic acid adduct extract, which is being developed aiming to be further applied in the food industry. An anthocyanin extract from blueberry (extract I) and an anthocyanin-pyruvic acid adduct extract (extract II) were tested on two breast cancer cell lines (MDA-MB-231 and MCF7). Proliferation was assessed by SRB assay and 3 Hthymidine incorporation. Caspase-3 activity was determined in the presence of both extracts. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(67 citation statements)
references
References 30 publications
2
65
0
Order By: Relevance
“…Blueberry anthocyanins and anthocyanin-pyruvic acid adduct extracts (250 μg/ml) demonstrated anti-invasive potential in both breast cancer cell lines, MDA-MB-231 and MCF7 [76]. The extracts inhibited proliferation of cancer cell by acting as chemoinhibitors.…”
Section: Nutraceutical and Pharmaceutical Effects Of Anthocyaninsmentioning
confidence: 99%
“…Blueberry anthocyanins and anthocyanin-pyruvic acid adduct extracts (250 μg/ml) demonstrated anti-invasive potential in both breast cancer cell lines, MDA-MB-231 and MCF7 [76]. The extracts inhibited proliferation of cancer cell by acting as chemoinhibitors.…”
Section: Nutraceutical and Pharmaceutical Effects Of Anthocyaninsmentioning
confidence: 99%
“…Extracts of Vaccinium myrtillus L. (Ericaceae) (bilberry, also known as European blueberry) have been found to be effective for inhibiting the growth of human leukemia, colon, and breast carcinoma cell lines as well as decreasing the number of intestinal adenoma in rats (Chu et al, 2011;Faria et al, 2010;Nguyen et al, 2010;Wu et al, 2007). The growth inhibitory and cytotoxic activity of bilberry fruit extracts on cancer cells are likely attributed to phenolic pigments, the anthocyanins, as bilberry fruits are one of the richest natural sources of these flavonoids and consumption of berries is the predominant means of anthocyanin ingestion (Chu et al, 2011;Katsube et al, 2003;Nguyen et al, 2010).…”
Section: Berriesmentioning
confidence: 99%
“…39 Lee et al demonstrated that morusin which is isolated from root bark of Morus australis and inhibits growth of human colon cancer cells via activation of caspases and inhibition of NF-κB pathway, 40 while Faria et al reported that blueberry antho cyanin-pyruvic acid adduct extract exhibits cytotoxic effect on human breast cancer cells via caspase activation. 41 In another study, albanol A from the root bark induces apoptosis in leukemia cells, 42 whereas…”
Section: Discussionmentioning
confidence: 99%